Market-wide Herding and the Impact of Institutional Investors in the Indian Capital Market. (August 2013) - Lakshman, M.V.; Basu, Sankarshan; Vaidyanathan, R.
The article tries to identify the presence of 'market-wide herding' in the Indian capital market and whether institutional investors impact such herding. In particular, the article looks at the impact of Foreign Institutional Investors flows as well as mutual funds on herding. The work also looks at the the impact of index return and volatility on herding. JEL Classification: G140, G180, C580, G120